2009
DOI: 10.5004/dwt.2009.500
|View full text |Cite
|
Sign up to set email alerts
|

Determination of target water quality indicators and values on total maximum daily loads management system in Korea

Abstract: ab s t r ac tTo improve the water quality of the four major rivers in Korea, Ministry of Environment of Korea (MOE) has introduced the Total Maximum Daily Loads (TMDLs) management system since 2002 and BOD was selected as one of the target materials during the first period (2004)(2005)(2006)(2007)(2008)(2009)(2010). For an effective watershed management, it is necessary to have one or more quantitative measures that can be used to evaluate the relationship between pollutant sources and their impacts on water q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Osnovni ciljevi ovog zakona su: obnavljanje i održavanje hemijskog, fizičkog i biološkog integriteta svih voda, obezbeđivanje kvaliteta vode u cilju zaštite i održanja biodiverziteta i moguće korišćenje vode za rekreaciju i kontrola ispuštanja zagađujućih materija. Vodeći princip kod obnavljanja oštećenih akvatičnih ekosistema u SAD je princip maksimalnog dnevnog opterećenja (Total Maximum Daily Loads, TMDL), koji je primenljiv kako za tačkaste tako i za difuzne zagađivače [19]. TMDL predstavlja najveću količinu opterećenja koje vodno telo može da primi, a da ne dođe do prekoračivanja vrednosti propisanih standardom kvaliteta voda i čini ga suma individualnih opterećenja iz koncentrisanih izvora i opterećenja iz rasutih izvora uključujući opterećenje koje potiče iz prirode, sa uračunatom granicom sigurnosti (nesigurnost u vezi sa odnosom između opterećenja zagađivačima i kvaliteta vode vodoprijemnika ili merna nesigurnost) [20,21].…”
Section: Naučni Radunclassified
“…Osnovni ciljevi ovog zakona su: obnavljanje i održavanje hemijskog, fizičkog i biološkog integriteta svih voda, obezbeđivanje kvaliteta vode u cilju zaštite i održanja biodiverziteta i moguće korišćenje vode za rekreaciju i kontrola ispuštanja zagađujućih materija. Vodeći princip kod obnavljanja oštećenih akvatičnih ekosistema u SAD je princip maksimalnog dnevnog opterećenja (Total Maximum Daily Loads, TMDL), koji je primenljiv kako za tačkaste tako i za difuzne zagađivače [19]. TMDL predstavlja najveću količinu opterećenja koje vodno telo može da primi, a da ne dođe do prekoračivanja vrednosti propisanih standardom kvaliteta voda i čini ga suma individualnih opterećenja iz koncentrisanih izvora i opterećenja iz rasutih izvora uključujući opterećenje koje potiče iz prirode, sa uračunatom granicom sigurnosti (nesigurnost u vezi sa odnosom između opterećenja zagađivačima i kvaliteta vode vodoprijemnika ili merna nesigurnost) [20,21].…”
Section: Naučni Radunclassified
“…Non-point source pollutants are difficult to determine, being even more difficult than point source pollutants [1]. Especially in areas near rivers and lakes, non-point source pollutants were influent water systems without any management to decrease pollutants, which is one of the reasons why water quality of the water system has decreased [2][3][4]. Previous researches were reported that non-point source pollutant loads are higher than sewage treatment plant effluent [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Such measurable quantities are termed target water quality indicators [16]. Before developing the TMDLs for a river basin, applicable water quality indicators are supposed to be selected as target pollutants by the stage in order to manage the pollution loads in total basis.…”
Section: Introductionmentioning
confidence: 99%